2005
DOI: 10.1073/pnas.0407284102
|View full text |Cite
|
Sign up to set email alerts
|

The basic helix–loop–helix olig3 establishes the neural plate boundary of the trunk and is necessary for development of the dorsal spinal cord

Abstract: olig genes encode a previously unrecognized group of vertebratespecific basic helix-loop-helix transcription factors. As shown in mice, chickens, and zebrafish, two members of this group, olig1 and olig2, are involved in the differentiation of motoneurons and oligodendrocytes, but nothing is known about the role of the third member, olig3. Here, we show that olig3 plays an essential role in the establishment of the neural crest-lateral neural plate boundary. In zebrafish embryos, morpholino-induced olig3 inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…Furthermore, it was shown that the Delta-Notch downstream component Olig3 is implicated in cell fate decisions between ncc and sensory neuron fates at the neural plate border (Filippi et al, 2005). As mdkb affects formation of both cell types after overexpression and gene knockdown, we tested whether lateral inhibition might influence mdkb expression by looking at Delta-Notch deficient mib mutants.…”
Section: Discussion Mdkb Expression Is Regulated By Retinoid But Not mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it was shown that the Delta-Notch downstream component Olig3 is implicated in cell fate decisions between ncc and sensory neuron fates at the neural plate border (Filippi et al, 2005). As mdkb affects formation of both cell types after overexpression and gene knockdown, we tested whether lateral inhibition might influence mdkb expression by looking at Delta-Notch deficient mib mutants.…”
Section: Discussion Mdkb Expression Is Regulated By Retinoid But Not mentioning
confidence: 99%
“…Delta-Notch signaling by means of the basic helix-loop-helix transcription factor Olig3 is crucial for establishing cell fate decision into the ncc vs. sensory neuron lineage at the neural plate border (Filippi et al, 2005). To investigate whether mdkb expression is influenced by Delta-Notch signaling, we analyzed its expression in zebrafish mindbomb (mib ta52b ) mutants.…”
Section: Regulation Of Mdkb Expression During Neural Crest Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third member, Olig3, is expressed in defined cell populations in the developing neural tube, among them dorsal progenitors (Takebayashi et al, 2002b). Recent work has demonstrated that Olig3 expression in the spinal cord is controlled by dorsal patterning signals, and that Olig3 is required to determine neuronal fates in the spinal cord of mice and zebrafish (Filippi et al, 2005;Muller et al, 2005;Zechner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%